Abrupt generalized pustules in patients with rheumatoid arthritis and interstitial lung disease. Issue 2 (23rd November 2017) - Deng, Wei; Miao, Chaoyang; Zhang, Xiaoyan
Abstract: We report a case of a 30‐year‐old Chinese woman with rheumatoid arthritis and interstitial lung disease who abruptly developed generalized pustules and a high fever for 10 days. She had been taking oral prednisone, iguratimod and total glucosides of peony regularly for 5 months prior. In addition, she had taken metronidazole for 3 days 20 days prior which she had used before with no adverse reaction. She had no history of similar lesions and psoriasis. A biopsy of a pustule on the back showed spongiform pustule of Kogoj. She was suspected of having generalized pustular psoriasis or acute generalized exanthematous pustulosis. Finally, she was diagnosed with generalized pustular psoriasis (von Zumbusch type) considering the characteristics and clinical course of the rash. In addition to the above three drugs, systemic cyclosporin (5 mg/kg per day) was applied, and the lesions and fever resolved within the proceeding 2 months.